Kierkegaard’s Sociality of Silence - Rasmussen, James P. (Kierkegaard studies. Yearbook, 2025)
This article explores the social dimension of silence in two sets of Kierkegaard’s discourses on the lilies and the birds, from 1847 and from 1849. This exploration is pursued through attention to the themes of emplacement and of breathing. The article shows that by 1849 Kierkegaard conceived of our emplacement, and also of the silence in which we affirm our emplacement, as shared: in finding the moment and finding the place, we also find fellow creatures sharing it with us. The sociality of silence Kierkegaard affirms here finds its basis not in comparison but in the recognition of shared emplacement.